(untitled) (Annals of Medical Research, 2025)
Aim: This study aimed to investigate the relationship between health literacy, digital healthy diet literacy, and dietary habits of pregnant women in different trimesters. Materials and Methods: This study included 189 pregnant women who had registered for routine prenatal care. The participants were interviewed about their demographic characteristics, general health, smoking and alcohol consumption, medical history, and general dietary habits. In addition, a questionnaire with the Health Literacy Scale and the Digital Healthy Diet Literacy Scale was completed. Results: A positive, weak, and statistically significant correlation was found between prepregnancy body mass index (BMI) and the Health Literacy Scale (p < 0.05). A positive, weak, and statistically significant relationship was found between health literacy and digital healthy eating literacy (r = 0.278; p = 0.007). Conclusion: As the health literacy of pregnant women improves, so does their digital healthy diet literacy. These results demonstrate the importance of promoting health literacy to support healthy dietary behaviors during pregnancy.